A Dynamic Approach to Performance for Software Development Projects - Díaz Vega, María Isabel; Ospina Ospina, Manuel José (Cuadernos de Administración, 2023)
This paper is based on analyzing the relationships between aspects that affect knowledge management and the performance of projects of micro and small companies dedicated to software development through a process of research, reflection, and application of system dynamics tools. For the realization, it was necessary to take data and models from a sector company and perform the analysis in two stages. In the first stage, an analysis was performed by reviewing the causal relationships through the first modeling of systemic thinking (feedback loops). In the second stage, modeling has been performed using Forrester diagrams. For the analysis, the variables for the study were identified, such as pending activities of a project, the productivity of the performed work, learning, and the development of code units that transform these requirements into functional programs. The result is the identification of variables, the relationships between them, and their incidence in the projects of micro and small companies dedicated to software development in Colombia. Likewise, the models used to evaluate the learning capacity and the knowledge management model should be analyzed to identify all types and areas that allow the development of projects. More factors affect this design than are currently known, so broader studies with a more complex model are recommended.